Marta's Identity (Journal of Parents and Teachers, 2024)
This article addresses the issue of identity construction and its implications in schools, specifically in Jesuit schools. It is written as a letter to a colleague describing a training in which she has participated.
Keywords: Christian identity; Ignatian identity; spiritual exercises